Educating Australia - Savage, Glenn Clifton (Melbourne University Publishing, 2017)
Where is Australian schooling headed? What forces will shape its future direction? How ready are students, teachers, policy makers and education institutions for the challenges being thrust on them? In this edited collection, these questions are addressed by some of Australia's leading education researchers, practitioners and policy entrepreneurs. With diverse chapters ranging from music education to equity and assessment in senior secondary education, from how to support school-based collaboration to preparing teachers to exercise professional judgment, this book provides a grounded, forward-looking overview of issues that will be central to Australia's educational debates, and our performance, in the years ahead. Drawing directly on research, innovation and policy analysis at the Melbourne Graduate School of Education, this book creates an engaging and rigorous overview of the issues confronting school-age education in Australia, and provides insights and actions to help shape our responses into the future.